NEW APPROACHES OF PREVENTIVE MAINTENANCE AND REHABILITATION, PATIENTS WITH UROLITHIASIS AFTER THE REMOTE LITHOTRIPSY WITH APPLICATION OF NEW VEGETATIVE GATHERING - I. R. Musin (Креативная хирургия и онкология, 2017)
The purpose of  the  present research to raise efficiency of  treatment and  preventive maintenance of  relapses  of  patients with  urolithic  illness after a  remote lithotripsy  by application of the developed rehabilitation complexes  on the basis of phytomeans.Work  is based  on  application of  own  patent with  use  of  phytomeans (the  Way of preventive  maintenance and complex treatment urolithic illness after a remote lithotripsy, the positive decision on delivery of the patent for the invention from 27.05.11г.) . Research is based on the clinical material including experience of treatment of 127 patients with urolithic illness from  2009  for 2010 the basic group  of 66 patients (with  application of an offered technique of complex treatment) and control group of 61 patients Has been generated. The analysis of results of treatment has shown  that  application of phytogathering for patients with urolithic illness after a remote lithotripsy promotes a conclusion  of stones, there  is an early knocking  over of inflammatory changes, phytogathering doesn’t  break  a functional condition of kidneys.  At the  same  time under  the  influence of phytogathering there  was statistically authentic increase  in volume of urine, decrease in level of nitrogenous slags (a Creatinine, urea), the tendency to decrease in the raised concentration of uric acid in whey of blood and the maintenance in urine of oxalates and uric acid Besides, isn’ted.